Association of childhood blood-lead levels with cognitive function and socioeconomic status at age 38 years and with IQ change and socioeconomic mobility between childhood and adulthood - Reuben, Aaron (JAMA, 2017)
IMPORTANCE: Many children in the US and around the world are exposed to lead, a developmental neurotoxin. The long-term cognitive and socioeconomic consequences of lead exposure are uncertain. OBJECTIVE: To test the hypothesis that childhood lead exposure is associated with cognitive function and socioeconomic status in adulthood and with changes in IQ and socioeconomic mobility between childhood and midlife. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study based on a population-representative 1972–73 birth cohort from New Zealand, the Dunedin Multidisciplinary Health and Development Study, followed to age 38 years (December, 2012). EXPOSURE: Childhood lead exposure ascertained as blood-lead levels measured at 11 years. High blood-lead levels were observed among children from all socioeconomic status levels in this cohort. MAIN OUTCOMES AND MEASURES: The IQ (primary outcome) and indexes of Verbal Comprehension, Perceptual Reasoning, Working Memory, and Processing Speed (secondary outcomes) were assessed at 38 years using the Wechsler Adult Intelligence Scale–IV (WAIS-IV; IQ range 40–160). Socioeconomic status (primary outcome) was assessed at 38 years using the New Zealand Socioeconomic Index-2006, (NZSEI-06; range 10=lowest-90=highest). RESULTS: Of 1037 original participants, 1007 were alive at 38 years, of whom 565 (56%) had been lead tested at 11 years (54% male; 93% white). Mean blood-lead level at 11 years was 10.99μg/dL (SD=4.63). Among blood-tested participants included at 38 years, mean WAIS-IV score was 101.16 (SD=14.82) and mean NZSEI-06 score was 49.75 (SD=17.12). After adjusting for maternal IQ, childhood IQ, and childhood socioeconomic status, each 5μg/dL higher level of blood-lead in childhood was associated with a 1.61-point lower score (95%CI:−2.48, −0.74) in adult IQ, a 2.07-point lower score (95%CI: −3.14, −1.01) in Perceptual Reasoning, and a 1.26-point lower score (95%CI: −2.38, −0.14) in Working Memory. Lead-associated deficits in Verbal Comprehension and Processing Speed were not statistically significant. After adjusting for confounders, each 5μg/dL higher level of blood-lead in childhood was associated with a 1.79-unit lower score (95%CI: −3.17, −0.40) in socioeconomic status. An association between greater blood-lead levels and a decline in IQ and socioeconomic status from childhood to adulthood was observed, with 40% of the association with downward mobility mediated by cognitive decline from childhood. CONCLUSION AND RELEVANCE: In this cohort born in New Zealand in 1972–1973, childhood lead exposure was associated with lower cognitive function and socioeconomic status at age 38 years and with declines in IQ and downward social mobility. Childhood lead exposure may have long-term ramifications.